Seminar on sustainability: scheduled waste management and the role of competent persons - Abdul Hamid, Hisyam (Faculty of Pharmacy, 2025)
The Ecopharmacovigilance Research Initiative Group (EcoPharma), in collaboration with the UiTM Pharmacy Analytical Laboratory (UiPAL), successfully organized a knowledge-sharing session entitled “Seminar Kelestarian: Peranan Pengurusan Sisa Berjadual dan Kepentingan Orang Kompeten Berkelayakan di dalam Industri” on 20th August 2025. The two-hour session, held from 10.00 am to 12.00 pm, featured Mr. Ts. Zaidi bin Mohamed @ Awang, a certified trainer from Institut Alam Sekitar (EiMAS), as the invited speaker.